Avaliação dosimétrica em superfície para braquiterapia de alta taxa de dose utilizando filmes radiocrômicos - Juan Carlos Chrisostomo Lamônica (2023)
The monitoring of radiation doses received during the radiotherapeutic treatment of oncology patients is of utmost importance to ensure the safety and effectiveness of the procedure. In vivo dosimetry allows for the direct measurement of radiation dose in the patient during radiotherapeutic treatment. However, its proper application depends on previous dosimetric studies for subsequent use in clinical conditions. In this study, an investigation of the in vivo dosimetry process was conducted, focusing on the high-dose-rate (HDR) brachytherapy modality for the treatment of skin lesions, using phantom objects and EBT3 radiochromic films. For this purpose, an applicator consisting of 15 synthetic material spheres was designed and developed. A Ir-192 brachytherapy source and solid water plates were used to simulate the treatments through a treatment planning system (TPS). The irradiated films were evaluated by scanning and reading using the ImageJ and Origin programs for analysis of the generated images. The dosimetry system was calibrated, and irradiations based on experimental arrangements were performed to evaluate the dose behavior in various situations: two-dimensional dose distribution, depth dose profile, dose attenuation with lead, and dose behavior in applicator junction regions when it is necessary to irradiate regions close to an already irradiated area. The results demonstrated the suitability of the proposed system, as the measured dose on the applicator surface and the percentage of dose at depth corresponded to the values provided by the TPS, in addition to the calibration. In the study of the depth dose percentage, a decrease in dose from the surface of the applicator was observed, as expected from the planning. Considering the protection of areas of interest during treatment, it was shown that the use of 1 mm of lead near the irradiated region increases the dose values by up to 31.9% above the prescribed value, highlighting that lead plates of this thickness should be covered with tissue-equivalent material (bolus) to absorb the extra dose in the vicinity of the plate. It was found that it is advisable to consider a distance of 5 mm between the positions assumed by the applicator when contiguous regions are irradiated. Thus, the dosimetry system for HDR modality proved promising for potential in vivo treatment control.